Utilização dos recursos florais por abelhas do gênero Xylocopa Latreille, 1802 (Hymenoptera, Apidae) em um ambiente de restinga no Litoral Norte na Bahia - Figueiredo, Nívia Almeida (2010)
Larger bees, such as Xylocopa spp., are common pollination of plant species from these habitats. Given the ecological importance of coastal plains and sand dunes ecosystem, this study aimed to evaluate the interactions between bees of the genus Xylocopa and the plants providing floral resources focusing on how the interplay of morphology and temporal pattern affect floral visitation. This study was carried out in Baixio, Esplanada, BA (North Coast Environmental Protection area). Monthly, from April 2008 to March 2009, during two consecutive days the bees were collected for 5 to 10 min. in each flowering plant. Throughout the study photos of the plants visited were taken and plant specimens collected. A total of 366 individuals of Xylocopa spp. were collected belonging to the following species: X. cearensis, X. frontalis, X. subcyanea and X. suspecta. Xylocopa cearensis had the largest number of individuals collected and was present during all study. This species also presented the greatest diversity of floral resources used, followed by X. subcyanea. These bees were of similar size and used many floral resources in common, as indicated by the similarity index in the use of plants. Both bees visited chiefly a few plant species to collect floral resources, such as Cuphea brachiata, Croton sellowii, Waltheria cinerascens and Chamaecrista ramosa. The highest number of X. cearensis individuals was recorded during the dry season. Both in wet and dry season, C. brachiata and C. sellowii were the plant species most used by X. cearensis and X. subcyanea. In the coastal dunes, Xylocopa bees are important pollinators, a few and abundant plant species such as C. brachiata and C. sellowii play a key role maintaining the population of Xylocopa spp. throughout the year.